Small area estimation and hotspot identification of opioid use disorder among military veterans living in the Southern United States. Issue 1 (2nd January 2021) - Albright, David L.; McDaniel, Justin; Kertesz, Stefan; Seal, David; Prather, Katie; English, Thomas; Laha-Walsh, Kirsten
Abstract: Background: The purpose of this study was to estimate opioid use disorder prevalence rates at the county level among veterans in Alabama and to determine hotspots of said rates. Methods: By combining data from the National Survey on Drug Use and Health and the American Community Survey, we developed a mixed-effects generalized linear model of opioid use disorder and modeled probabilities onto veteran-specific population counts at the county level in Alabama. Results : The average model-based estimate for opioid use disorder prevalence among veterans in Alabama from 2015 to 2017 was 0.79% ( SD  = 0.16), with a minimum of 0.52% (i.e., Lowndes county, Alabama) and a maximum of 1.10% (Dale county, Alabama). Hotspot analysis revealed a significant cluster of "high-high" veteran opioid use disorder prevalence in neighboring Marion, Winston, and Cullman counties. Conclusions : The application of the statistical technique presented in this study can provide feasible, cost-effective, and practical county-level prevalence estimates of veteran-specific opioid use disorder and should be widely applied by states and counties so that they can more accurately and efficiently allocate resources to caring for veterans with an opioid use disorder.